The teaching of mathematical knowledge for teaching – a learning study of primary school teacher education - Bommel, Jorryt van (NOMAD Nordic Studies in Mathematics Education, 2014)
A group of Swedish teacher educators conducted a learning study in order to identify critical features concerning the teaching and learning of Mathematical knowledge for teaching (MKT). Three seminars and 300 tests were analysed using variation theory revealing four critical features to take into account in teaching student teachers in mathematics education: namely their need to i) formulate proper goals for a lesson, ii) outline the lesson plan in detail, iii) shift perspective from the role of being a teacher to being a mathematics teacher, and iv) understand the underlying mathematics of the lesson topic at hand. Thus, these are the four features of importance to the learning and teaching of MKT.